Teaching music in basic education: understanding the role of teaching from the perspective of an intern on a music degree course (Orfeu, 2024)
This paper aims to investigate how the intern of the bachelor degree program in music education construct understandings about the role of teaching music in basic education. Based on the studies of Maria do Céu Roldão on teaching professionality, it was carried out through a document analysis, taking as its empirical material the internship portfolio prepared by a music education student. Results indicate that the intern's understanding is constructed over time, from the encounters in the internship field, with students, teachers and school, the encounter with himself and the collective mentoring meetings at the university. The more encounters in the internship field, the greater is the possibility of building broader understandings; however, the transformations of the intern's understanding depend on the expansion of knowledge and the activation of the generators of specificity of professional teaching knowledge, which are driven by the mentoring. Thus, it is from the interaction between the space of professional practice and the university that the function of teaching music in basic education is understood in its complexity.
Keywords: internship in bachelor de-gree program in music education; school music teaching; role of the teaching pro-fession; teaching professionality